The ellagic acid-derived gut microbiota metabolite, urolithin A, potentiates the anticancer effects of 5-fluorouracil chemotherapy on human colon cancer cells. Issue 5 (13th May 2015) - González-Sarrías, Antonio; Tomé-Carneiro, Joao; Bellesia, Andrea; Tomás-Barberán, Francisco A.; Espín, Juan Carlos
<x xml:space="preserve">Abstract</x> The ellagic acid-derived gut microbiota metabolite, urolithin A, at concentrations achievable in the human colorectum, enhances the anticancer effects of 5-FU-chemotherapy on three different colon cancer cells.